Evaluation role of Serum uric acid to creatinine ratio as a useful predictor of renal dysfunction among diabetic patients type 2 - صبح, علي; رمال عبد العزيز أسعد , (Latakia University Journal -Medical Sciences Series, 2023)
Objective: To study the presence of a relationship between the serum uric acid / creatinine ratio (SUA/Cr) and annual eGFR decline rate to predict kidney damage incidence among patients with T2DM. Study design: This study was conducted on 118 adults with type 2 diabetes mellitus at Tishreen University Hospital and Diabetes Care Center in Latakia / Syria. The study form was filled out after the patients 'acceptance. HbA1c, uric acid, Creatinine, fasting blood glucose, and lipid profile were measured for patients. We calculated the initial SUA/Cr (from which the patients were divided according to this ratio into 4 groups), eGFR (beginning and after 6 months), and annual eGFR decline rate. We studied the existence of a relationship between SUA/Cr and the annual eGFR decline rate, and SUA/Cr with each of : systolic and diastolic blood pressure, BMI, waist circumference, sex, duration of diabetes, lipid formula, HbA1c, and fasting blood glucose. Results: The results obtained showed a statistically significant positive correlation between the annual eGFR decline rate and the uric acid/creatinine ratio (r=0.34, p=0.01), a statistically significant positive correlation between uric acid/creatinine ratio and waist circumference (r=0.38, p=0.001), a statistically significant negative correlation between the uric acid/creatinine ratio and both HbA1c (r = -0.30, p = 0.001) and fasting blood glucose in patients (r = -0.36, p = 0.00), But There were no statistically significant differences between the groups and each of: systolic and diastolic blood pressure, BMI, duration of diabetes, lipid formula, sex.